Identifying challenges in the postharvest supply chain of fresh organic produce - Tricia Jenkins; Londa Nwadike; Manreet Bhullar; Cary Rivard; Candice Shoemaker; Elizabeth Mitcham; Jeffrey Brecht; Angelos Deltsidis; Eleni Pliakoni (Urban Food Systems Symposium, 2022)
The production of organic produce has been steadily increasing in the United States in recent years. The use of appropriate postharvest practices on small-acreage organic farms and urban farms is critical for minimizing postharvest losses and ensuring the safety of fresh produce. The objectives of this project were to (i) gain a better understanding of the critical needs that organic growers and industry buyers are facing regarding postharvest handling and safety of their produce (ii) identify the factors limiting produce quality, shelf-life, and microbial safety (iii) identify critical areas in postharvest handling, processing, and food safety of organic produce for targeted research, education, and extension work. A mixed methods qualitative study design was used to meet the project objectives. A national online survey was administered to organic produce growers (n=68). An asynchronous and synchronous online focus group (n=8) of organic produce growers was conducted to further explore some of the main themes from the online survey results. The results from the survey indicated that postharvest loss of fresh produce can range from 1% to above 20% of the total crop, with the most typical losses being between 1% and 5%. Growers believe that proper temperature management is the most important factor that affects postharvest quality of organic fruits, vegetables, and herbs. The sample cited that a lack of knowledge and financial constraints were the greatest barriers to adopting or improving postharvest handling practices. Similarly, low-cost solutions and infrastructure were the most-needed research needs by growers. The focus group (n=8) elaborated on knowledge constraints in postharvest handling, saying it was difficult to search the web and find reliable information. The focus group agreed that a central website hub that had searchable and dependable postharvest handling information would be a valuable resource to them. The results from this mixed-method approach will guide future research and extension programming with the long-term goal of providing small-acreage organic produce growers with appropriate postharvest handling practices that will reduce postharvest losses, improve food safety, and ultimately increase the availability of organic produce.